2006
DOI: 10.1002/prop.200510277
|View full text |Cite
|
Sign up to set email alerts
|

Chronology protection in AdS/CFT

Abstract: We review the issue of chronology protection and show how string theory can solve it in the half BPS sector of AdS/CFT. According to the LLM prescription, half BPS excitations of AdS5 × S 5 geometries in type IIB string theory can be mapped into free fermion configurations. We show that unitarity of the theory describing these fermions is intimately related to the protection of the chronology in the dual geometries.Copyright line will be provided by the publisher The principle of causality stands at the founda… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…An intriguing observation has been made by the authors of [25] and [26], that from the point of view of the AdS/CFT correspondence, the existence of CTC in the bulk can be related to negative or exceeding one fermionic probability in the boundary field theory. Per contra, in [27] it was demonstrated that, by deforming AdS 5 × S 5 spacetime in a certain way, it is possible to construct a supergravity solution possessing CTC confined to the bulk, such that the stress-energy tensor of the dual boundary N ¼ 4 superYang-Mills theory remains well defined and finite.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An intriguing observation has been made by the authors of [25] and [26], that from the point of view of the AdS/CFT correspondence, the existence of CTC in the bulk can be related to negative or exceeding one fermionic probability in the boundary field theory. Per contra, in [27] it was demonstrated that, by deforming AdS 5 × S 5 spacetime in a certain way, it is possible to construct a supergravity solution possessing CTC confined to the bulk, such that the stress-energy tensor of the dual boundary N ¼ 4 superYang-Mills theory remains well defined and finite.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we address this problem and by use of the AdS/CFT correspondence provide a constructive solution to it. Here we stand on the position that even if the presence of CTC causes breaking of unitarity in the boundary field theory [26], it should not be regarded as a big problem as long as we can formulate a prescription how to solve the theory. When one is trying to get an insight into physics of paradoxical systems, it is not very useful to rely on the "common sense" intuition and corresponding fundamental principles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation